Rola rodziców w rozwoju dziecka niesłyszącego - Jagoszewska, Iwona (Karkonoska Państwowa Szkoła Wyższa, 2011)
Both the parents and the deaf children live with a disability. The specificity of deafness has a significant impact on the functioning of the families which often requires support of their care and educational functions. Therefore, it is vital to establish a cooperation between parents and proper institutions and specialists. Hearing dysfunction requires intensification of parents actions in the field of recognizing and developing the strong sides of deaf child.
Keywords: niesłyszący; dzieci; rodzice; komunikacja; niepełnosprawność